Core implementation strategies for improving cirrhosis care in the Veterans Health Administration. Issue 2 (17th March 2022) - Yakovchenko, Vera; Morgan, Timothy R.; Miech, Edward J.; Neely, Brittney; Lamorte, Carolyn; Gibson, Sandra; Beste, Lauren A.; McCurdy, Heather; Scott, Dawn; Gonzalez, Rachel I.; Park, Angela M.; Powell, Byron J.; et al.
Abstract: Background and Aims: The Veterans Health Administration (VHA) provides care for more than 80, 000 veterans with cirrhosis. This longitudinal, multimethod evaluation of a cirrhosis care quality improvement program aimed to (1) identify implementation strategies associated with evidence‐based, guideline‐concordant cirrhosis care over time, and (2) use qualitative interviews to operationalize strategies for a manualized intervention. Approach and Results: VHA providers were surveyed annually about the use of 73 implementation strategies to improve cirrhosis care in fiscal years 2018 (FY18) and 2019 (FY19). Implementation strategies linked to guideline‐concordant cirrhosis care were identified using bivariate statistics and comparative configurational methods. Semistructured interviews were conducted with 12 facilities in the highest quartile of cirrhosis care to specify the successful implementation strategies and their mechanisms of change. A total of 106 VHA facilities (82%) responded at least once over the 2‐year period (FY18, n = 63; FY19, n = 100). Facilities reported using a median of 12 (interquartile range [IQR] 20) implementation strategies in FY18 and 10 (IQR 19) in FY19. Of the 73 strategies, 35 (48%) were positively correlated with provision of evidence‐based cirrhosis care. Configurational analysis identified multiple strategy pathways directly linked to more guideline‐concordant cirrhosis care. Across both methods, a subset of eight strategies was determined to be core to cirrhosis care improvement and specified using qualitative interviews. Conclusions: In a national cirrhosis care improvement initiative, a multimethod approach identified a core subset of successful implementation strategy combinations. This process of empirically identifying and specifying implementation strategies may be applicable to other implementation challenges in hepatology. Abstract : image